Daily of people supplied by hanseniasis in compulsory insulation in Hospital Colony - Camila Xavier de Melo; Raphaela Delmondes do Nascimento; Taysa Viera de Almeida; Nathalie mendes Estima; Jailma Ferreira de Vasconcelos; Mirian Domingos Cardoso (Universidade de Pernambuco, 2019)
Objective: To learn about the daily lives of people affected by institutionalized leprosy during compulsory isolation at Hospital Colônia Padre Antônio Manoel, in Paulista-PE. Methods: Qualitative-descriptive study. Semi-structured interviews were carried out with people who were part of the hospital's daily routine during this period. The interviews were conducted using an interview guide prepared by the authors, after the subjects' agreement. Results: The results were organized according to the categories: Work activities developed by users; Expressions of culture and leisure and Striking facts. Conclusion: After conducting this study, it was possible to learn how people affected by leprosy spent their days in a "world apart", segregated from society.